Adolescent lives in transition : how social class influences the adjustment to middle school - San Antonio, Donna Marie, 1951- (State University of New York Press, 2004)
"Addressing the issues of educational equity and social class diversity, Donna Marie San Antonio documents the challenges adolescents face when making the transition from elementary school to middle school. The book explorers the values, resources, and ways of interacting that students from diverse economic backgrounds bring from their families and communities, and how they are enabled or discouraged from integrating these assets in their new school environments."--Jacket